Resident Perceptions of Sustainable Tourism Development in Borobudur Temple Tourist Destination - Kusherdyana (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2021)
The resident’s perception of the impact of tourism development is an important factor for the planning, management and development of a tourism destination. A positive perception of the impact of tourism will encourage residents to support and participate in tourism development, on the contrary, a negative perception of the impact of tourism causes residents accusers to be unsupportive and have no desire to participate in tourism development in the region. Therefore, this study aims to analyze the positive and negative perceptions of residents and their influence on the support and participation of sustainable tourism development. Using a qualitative approach, the data is collected by conducting in-depth interviews with residents around Borobudur Temple Tourist Destinations (BTTD) amount of 23. The results showed that residents have a positive perception of tourism development. They are very supportive and have a desire to participate in the development of tourism. The implication for the local government and the manager is to involve the residents more in the planning and development of BTTD. Keywords: Resident’s Perception; Resident’s support and participation; Sustainable Tourism Development; Borobudur Temple Tourist Destination.